Geographical information systems theory, applications and management : first International Conference, GISTAM 2015, Barcelona, Spain, April 28-30, 2015, Revised selected papers /: first International Conference, GISTAM 2015, Barcelona, Spain, April 28-30, 2015, Revised selected papers. (2016) - Unknown
No abstract available